Influence of the cover layer of underground metallic construction on the efficiency of cathode protection - V. G. Kiselev; A. A. Kalyutik (Известия высших учебных заведений: Проблемы энергетики, 2017)
Work examines the most probable mechanism of shaping of cover layer on the surface of the metallic communications of those finding in the soil or the sea water under the action of cathode protection and its basic properties. Being based on this analysis and data, obtained in the process of the practical operation of the systems of cathode protection both with respect to the change in the electrical conductivity of cover layers and on reduction in the strength of shielding current, a evaluation of a change in the efficiency (efficiency) of cathode protection in the direct-current circuit is made. In this case it is established that this efficiency grows with an increase in the specific resistance of cover layer on the surface of the protected metallic construction and connected with this reduction in the specific density of shielding current.